대향류 확산 화염 모델에서의 압력 및 산소분율에 따른 연소 특성 변화에 관한 수치해석 연구 - 박진제(Jinje Park); 이영재(Youngjae Lee) (Clean Technology, 27(1), 2021)
As the seriousness and necessity of responding to climate change and reducing carbon emissions increases, countries around the world are continuing their efforts to reduce greenhouse gases. Among various efforts, research on CCUS, capturing and utilizing carbon dioxide generated when using carbon-based fuels, is actively being conducted. Studies on pressurized oxy-fuel combustion (POFC) that can be used with CCUS are also being conducted by many researchers. The purpose of this study is to analyze basic information related to the flame structure and pollutant emissions of pressurized oxy-fuel combustion. For this, a counter-flow diffusion flame model was used to analyze the combustion characteristics according to pressure and oxygen concentration. As the pressure increased, the flame temperature increased and the flame thickness decreased due to a reaction rate improvement caused by the activation of the chemical reaction. As oxygen concentration increased, both the flame temperature and the flame thickness increased due to an improvement to the reaction rate and diffusion because of a change in oxidizer momentum. Analyzing the related heat release reaction by dividing it into three sections as the oxygen concentration increased showed that the chemical reaction from the oxidizer side was subdivided into two regions according to the mixture fraction. In addition, the emission index of NO classified according to the NO formation mechanism was analyzed. The formation trend of NO according to each analysis condition was presented. 기후변화 대응과 탄소배출 저감에 대한 심각성 및 필요성이 중요시 되면서 세계 각국은 온실가스를 감축하고자 하는 노력을 지속하고 있다. 다양한 노력들 중 탄소기반 연료 사용 시 발생되는 이산화탄소를 포집하여 활용하는 CCUS에 대한 연구가 활발히 진행되고 있으며, 이러한 관점에서 CCUS와 함께 활용될 수 있는 가압 순산소 연소에 대한 연구도 여러 연구자들에 의해 진행되고 있다. 본 연구는 가압 순산소 연소의 화염 구조와 오염물질 배출과 관련된 기초적인 정보를 분석하는데 목적이 있다. 이를 위해 대향류 확산 화염 모델을 이용하여 압력 및 산소분율에 따른 연소의 특성을 분석한 결과, 압력이 높을수록 화학 반응의 활성화로 인한 반응율의 증가로 연소 온도가 증가하고 화염두께는 감소한 반면, 산소분율이 높을수록 반응율 증가 및 산화제 운동량 변화에 따른 확산의 영향으로 연소 온도 및 화염두께 모두 증가하였다. 이와 관련된 열방출 반응을 3가지 구간으로 구분하여 분석한 결과, 특히 산소분율이 증가할수록 산화제 측면에서 나타나는 화학 반응이 혼합분율에 따라 크게 두 개의 영역으로 세분화되는 특성이 나타났다. 또한, NO의 생성 메커니즘에 따라 구분된 배출지수(EINO)를 분석하였고, 각 해석 조건에 따른 NO의 생성 경향을 제시하였다.